A propensity score weighted comparison of vedolizumab and adalimumab in Crohn's disease. Issue 1 (8th June 2020) - Macaluso, Fabio Salvatore; Ventimiglia, Marco; Fries, Walter; Viola, Anna; Sitibondo, Aldo; Cappello, Maria; Scrivo, Barbara; Busacca, Anita; Privitera, Antonino Carlo; Camilleri, Salvatore; Garufi, Serena; Di Mitri, Roberto; et al.
Abstract: Background and Aim: There are no head‐to‐head randomized controlled trials between biologics in Crohn's disease (CD). We aimed to perform a multicenter, real‐life comparison of the effectiveness of vedolizumab (VDZ) and adalimumab (ADA) in CD. Methods: Data of consecutive patients with CD treated with VDZ and ADA from January 2016 to April 2019 were extracted from the cohort of the Sicilian Network for Inflammatory Bowel Disease. The effectiveness was evaluated at 12, 52 weeks, and as failure‐free survival at the end of follow up. Propensity score analysis was performed using the inverse probability of treatment weighting method. Results: Five hundred eighty‐five treatments (VDZ: n = 277; ADA: n = 308) were included (median follow‐up: 56.0 weeks). After 12 weeks, a clinical response was achieved in 64.3% patients treated with VDZ and in 83.1% patients treated with ADA (odds ratio [OR] 0.65, 95% confidence interval [CI] 0.38–1.10, P = 0.107), while at 52 weeks, a clinical response was observed in 54.0% patients treated with VDZ and in 69.1% patients treated with ADA (OR 0.77, 95% CI 0.45–1.31, P = 0.336). Cox survival analysis weighted for propensity score showed no significant difference in the probability of failure‐free survival between the two drugs (hazard ratio = 1.20, 95% CI 0.83–1.74, P = 0.340). Post‐treatment endoscopic response and mucosal healing rates were similar between the two groups (endoscopic response: 35.3% for VDZ and 25.5% for ADA, P = 0.15; mucosal healing: 31.8% for VDZ and 33.8% for ADA, P = 0.85). Conclusions: In the first study comparing VDZ and ADA in CD via propensity score analysis, the drugs showed comparable effectiveness and a similar safety profile.